Underground heater insulating material capable of improving insulating property through manganese doping and preparation method of underground heater insulating material

By doping manganese elements into the insulating material of the underground high-power heater, a mixed material of manganese-containing doped materials and magnesium oxide is formed, and through a specific preparation process, the problem of insufficient insulation performance of existing insulating materials at high temperatures is solved. , achieving good insulation performance and stability at high temperatures.

CN119430870AActive Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411332469.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-14
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The thermal conductivity, thermal stability, insulation performance and long-term service performance of existing underground high-power heater insulation materials are limited by factors such as purity, chemical properties, particle shape, particle size distribution, crystal shape and filling process, and it is difficult to meet high temperatures. Good insulation performance requirements.

Method used

By doping manganese elements into the insulating material, a mixed material of manganese-containing doped material and magnesium oxide is formed, and insulating ceramic materials are prepared by ball milling, drying and granulation, aging and plastic discharge sintering and other processes.

Benefits of technology

It improves the density and strength of the insulating material, improves the high-temperature insulation performance, and ensures that it is not broken down at a high temperature of 650 degrees Celsius. It is suitable for insulating materials of downhole high-power heaters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430870A_ABST
    Figure CN119430870A_ABST
Patent Text Reader

Abstract

The invention discloses an underground heater insulating material capable of improving the insulating property through manganese doping and a preparation method thereof. The insulating material is an insulating ceramic material prepared from a mixed material containing magnesium oxide, a doping material containing a manganese element and a modifying reagent through ball milling, drying granulation, aging forming and plastic removal sintering. The doping material containing the manganese element and magnesium oxide can form a solid solution, so that crystal lattices of magnesium oxide crystals are activated, the compact degree and strength of the material are improved, and the insulating property is improved; the modification reagent reduces the vacancy defect of MgO crystal grains, moisture absorption is not easy to form an MgO-OH structure, and the volume resistivity is improved; compared with a high-purity magnesium oxide ceramic material, the prepared insulating ceramic material has good high-temperature insulating property and can be used as an insulating material for an underground high-power heater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of downhole high-power heaters and insulating materials, and in particular to a downhole heater insulating material with improved insulation performance through manganese doping and a preparation method thereof. Background Art

[0002] With the continuous increase in demand for oil and gas and the continuous consumption of conventional oil and gas resources, the effective development of unconventional oil and gas resources is of great strategic significance for alleviating the pressure on oil and gas resource supply and promoting the low-carbon transformation of energy structure and green development. Unconventional oil and gas mainly include heavy oil, shale oil, shale gas, coalbed methane, etc. Downhole electric heater technology is applied to new fields such as downhole heating assistance for heavy oil and underground in-situ coal gasification, which is of great significance to the implementation of major projects such as downhole electric heating assistance for heavy oil thermal recovery, in-situ conversion of shale oil, and underground in-situ coal gasification.

[0003] Downhole high-power electric heating technology uses the heat generated by resistance heating to continuously heat the heat transfer medium (steam, water or oil layer) in the wellbore. Downhole high-power electric heaters are the core equipment of electric heating technology. Electric heaters (mineral insulated heating cables) are mainly made of single or multiple resistance electric heating alloy wires as heat sources, magnesium oxide as thermal insulators, stainless steel or copper as sheaths, and are manufactured using special production processes. When current passes through the heating core wire, electrical energy is converted into thermal energy to heat the reservoir.

[0004] At present, electric heating technology mainly uses MI cable, in which the insulation material is high-purity magnesium oxide. However, due to the influence of many factors such as purity, chemical properties, particle shape, particle size distribution, crystal shape, filling process, etc., its thermal conductivity, thermal stability, insulation performance and long-term service performance are all limited. Therefore, it is of great practical significance to develop a preparation method for underground high-power heater insulation material, and make it have good insulation, mechanical strength, thermal conductivity and stability. Summary of the invention

[0005] In view of the above problems, the present invention proposes a downhole heater insulation material with improved insulation performance through manganese doping and a preparation method thereof, which overcomes the above problems or at least partially solves the above problems.

[0006] In the first aspect, an embodiment of the present invention provides a downhole heater insulating material with improved insulation performance through manganese doping, wherein the insulating material is an insulating ceramic material obtained by ball milling, drying and granulating, aging and sintering a mixed material containing magnesium oxide, a doping material containing manganese elements and a modifying agent.

[0007] Optionally, the mass content of the doping material containing manganese element in the mixed material is 0.5-2.7%, and the mass content of the modifying agent in the mixed material is 1-9%.

[0008] Optionally, the doping material containing manganese element is a manganese salt.

[0009] Optionally, the doping material containing manganese element is manganese oxide.

[0010] Optionally, the doping material containing manganese element is manganate.

[0011] Optionally, the doping material containing the manganese element is a coordination compound of manganese.

[0012] Optionally, the modifying agent is at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecyl sulfonate, CTAB and butyl titanate.

[0013] In a second aspect, an embodiment of the present invention provides a method for preparing an insulating material of a downhole heater with improved insulation performance by manganese doping, comprising:

[0014] A mixed material including magnesium oxide, a doping material containing a manganese element and a modifying agent is subjected to wet ball milling to obtain a slurry raw material;

[0015] Drying the slurry raw material and sieving it to obtain a powder material;

[0016] Adding a binder into the powder material for granulation, and then pressing it into a ceramic green body;

[0017] The ceramic green body is crushed, reshaped and aged to obtain a ceramic green sheet;

[0018] The ceramic green sheets are subjected to plastic disassembly and sintering to obtain insulating ceramic materials.

[0019] Optionally, after obtaining the ceramic green sheet, the process further comprises:

[0020] Determine whether the particle size of the current ceramic green sheet meets the particle size requirements;

[0021] If not, the current ceramic green sheet is used as the raw material and the process returns to the step of obtaining a slurry raw material through wet ball milling.

[0022] Optionally, the slurry raw material is obtained by wet ball milling, comprising:

[0023] The slurry raw material is obtained by wet ball milling with agate balls and anhydrous ethanol as media.

[0024] The beneficial effects of the above technical solution provided by the present invention include at least:

[0025] (1) The insulating material for underground heaters with improved insulation performance by manganese doping provided by the present invention is an insulating ceramic material obtained by ball milling, drying and granulation, aging and sintering of a mixed material containing magnesium oxide, a doping material containing manganese elements, and a modifying agent. Since the doping material containing manganese elements and magnesium oxide can form a solid solution, the lattice of magnesium oxide crystals is activated, the density and strength of the material are improved, and the insulation performance is improved; the modifying agent reduces the vacancy defects in the MgO grains, is not easy to absorb moisture to form a MgO-OH structure, and improves the volume resistivity; the obtained insulating ceramic material has good high-temperature insulation performance compared with high-purity magnesium oxide ceramic materials, and can be used as an insulating material for underground high-power heaters.

[0026] (2) The preparation method of the downhole heater insulation material with improved insulation performance by manganese doping provided by the present invention is simple, easy to operate, and suitable for industrial production.

[0027] The technical solution of the present invention is further described in detail below through embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0029] Figure 1 The present invention is a flow chart of a method for preparing downhole heater insulation material with improved insulation performance through manganese doping. DETAILED DESCRIPTION

[0030] The exemplary embodiments of the present invention are described in detail below. Although exemplary embodiments are disclosed, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0031] In order to solve the problems existing in the prior art, the present invention provides a downhole heater insulating material with improved insulation performance through manganese doping and a preparation method thereof.

[0032] The present invention provides an insulating material for a downhole heater with improved insulation performance through manganese doping. The insulating material is a uniform insulating ceramic material with good electrical resistance at high temperatures, which is prepared by ball milling, drying and granulation, aging and sintering of a mixed material containing magnesium oxide, a doping material containing manganese elements and a modifying agent.

[0033] Since the manganese-containing doping material and magnesium oxide can form a solid solution, the lattice of the magnesium oxide crystal is activated, the density and strength of the material are improved, and the insulation performance is improved; the modification reagent reduces the vacancy defects in the MgO grains, making it less likely to absorb moisture to form a MgO-OH structure, and the volume resistivity is improved; the obtained insulating ceramic material has good high-temperature insulation performance and can be used as an insulation material for underground high-power heaters, which can ensure that it will not be broken down at a high temperature of 650 degrees Celsius.

[0034] Optionally, the purity of the magnesium oxide is not less than 80%.

[0035] Optionally, the mass content of the doping material containing manganese element in the mixed material is 0.5-2.7%, and the mass content of the modifying agent in the mixed material is 1-9%.

[0036] Optionally, the doping material containing manganese element may be in the following forms:

[0037] (1) The doping material containing manganese is a manganese salt

[0038] It may be manganese acetate or manganese stearate, or may be manganese carbonyl, manganese tungstate, manganese citrate, manganese (II) trifluoromethanesulfonate, manganese (II) carbonate, manganese perchlorate, or the like.

[0039] (2) The doping material containing manganese is manganese oxide

[0040] It may be an oxide of various valence states of manganese, such as manganese monoxide, manganese dioxide, dimanganese trioxide, trimanganese tetraoxide, etc.; it may also be in the form of an oxide such as lithium manganese nickel oxide, lithium nickel manganese cobalt oxide, etc.

[0041] (3) The doping material containing manganese is a manganate

[0042] For example, barium manganate, potassium permanganate, or lithium permanganate (III, IV) or the like.

[0043] (4) The doping material containing manganese is a coordination compound of manganese

[0044] The cyclopentadienyl manganese (I) tricarbonyl and tetra-p-tolyl porphyrin manganese may be used, and di(ethylcyclopentadienyl) manganese (II) and tri(2,2,6,6-tetramethyl-3,5-heptanedioate) manganese (III) may be used.

[0045] Optionally, the modifying agent may be at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecyl sulfonate, CTAB and butyl titanate.

[0046] The present invention provides a method for preparing an insulating material for a downhole heater by improving the insulating performance through manganese doping, see Figure 1 As shown, the following steps are included:

[0047] Step S11: wet-milling a mixed material including magnesium oxide, a doping material containing a manganese element and a modifying agent to obtain a slurry raw material.

[0048] Among them, the specific materials and mass ratios of magnesium oxide, manganese-containing doping materials and modifying agents are described above.

[0049] The method may be to wet-mill the magnesium oxide raw material, the doping material containing the manganese element and the modifying agent for 6 to 12 hours using agate balls and anhydrous ethanol as the medium to obtain a slurry raw material.

[0050] Step S12: drying the slurry raw material and sieving it to obtain a powder material.

[0051] After the slurry raw material is dried, it is passed through a 40-100 mesh sieve to obtain the under-sieve powder material.

[0052] Step S13: adding a binder into the powder material for granulation, and then pressing it into a ceramic green body.

[0053] The binder is added into the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic green body.

[0054] Furthermore, the binder may be polyvinyl alcohol (PVA), and its mass fraction may be 5-10 wt. %; optionally, other binders may also be selected.

[0055] Step S14: crushing, reshaping and aging the ceramic green body to obtain ceramic green sheets.

[0056] Optionally, after obtaining the ceramic green sheet, the following steps may also be performed:

[0057] It is determined whether the particle size of the current ceramic green sheet meets the particle size requirement; if not, the current ceramic green sheet is used as a raw material and the process returns to the step of obtaining a slurry raw material through wet ball milling.

[0058] In the process of re-preparing ceramic green sheets using the current ceramic green sheets as raw materials, the previous preparation process may be kept unchanged, or agate balls with higher hardness may be selected, and / or a sieve with a smaller mesh size may be selected.

[0059] Step S15: sintering the ceramic green sheets to obtain insulating ceramic materials.

[0060] The method may include heating the formed ceramic green sheets to 500-700°C at a heating rate of 5°C / min, and maintaining the temperature for 30-120 minutes to perform a debinding treatment; then heating the ceramic green sheets to 1000-2000°C in a high-temperature muffle furnace, and maintaining the temperature for 1-48 hours to perform high-temperature sintering on the ceramic green sheets to obtain an insulating ceramic material.

[0061] The method for preparing the downhole heater insulation material with improved insulation performance through manganese doping provided by the present invention is simple, easy to operate, and suitable for industrial production.

[0062] Example 1

[0063] Weigh and add 1000g magnesium oxide (purity 99.99%), 10g manganese acetate, 10g sodium stearate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0064] Example 2

[0065] Weigh and add 1000g magnesium oxide (purity 99.99%), 20g manganese stearate, 20g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0066] Example 3

[0067] Weigh and add 1000g magnesium oxide (purity 99.99%), 5g manganese dioxide, 30g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0068] Example 4

[0069] Weigh and add 1000g magnesium oxide (purity 99.99%), 30g lithium manganese nickel oxide, 50g CTAB, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0070] Example 5

[0071] Weigh and add 1000g magnesium oxide (purity 99.99%), 10g barium manganate, 100g butyl titanate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0072] Example 6

[0073] Weigh and add 1000g magnesium oxide (purity 99.99%), 10g potassium permanganate, 10g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0074] Example 7

[0075] Weigh and add 1000g magnesium oxide (purity 99.99%), 10g tricarbonyl cyclopentadienyl manganese, 10g sodium dodecyl sulfonate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0076] Example 8

[0077] Weigh and add 1000g magnesium oxide (purity 99.99%), 10g tetra-p-tolylporphyrin manganese, 10g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill, and perform wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0078] Example 9

[0079] Weigh and add 1000g magnesium oxide (purity 99.99%), 5g manganese trioxide, 30g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill, and perform wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0080] Example 10

[0081] Weigh and add 1000g magnesium oxide (purity 80.00%), 5g manganese dioxide, 30g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0082] Embodiment 11

[0083] Weigh and add 1000g magnesium oxide (purity 90.00%), 5g manganese dioxide, 30g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0084] Example 12

[0085] Weigh and add 1000g magnesium oxide (purity 95.00%), 5g manganese dioxide, 30g sodium dodecyl sulfate, and an appropriate amount of anhydrous ethanol to a star-shaped ball mill for wet ball milling for 9 hours. Transfer the above raw materials to an oven, dry at 120°C for 24 hours, pass through a 40-mesh sieve, and add 5wt.% polyvinyl alcohol (PVA) as a binder to the powder for granulation. During the granulation process, the binder and the powder are fully mixed and then pressed into a ceramic blank. The ceramic blank is crushed, reshaped, and aged to obtain a ceramic green sheet. The formed ceramic green sheet is heated to 500°C at a heating rate of 5°C / min, and kept warm for 30 minutes for debinding treatment; then heated to 1400°C in a high-temperature muffle furnace and kept warm for 48 hours, and the ceramic green sheet is sintered at high temperature to obtain a ceramic sample.

[0086] The ceramic sheet is machined according to the sample size requirements of the performance to be tested. For samples for electrical performance testing, the surface of the processed ceramic sheet needs to be coated with silver electrodes and kept at 800°C for 30 minutes to complete the electrode firing, and then the corresponding electrical performance tests are carried out.

[0087] Taking the existing high-purity magnesium oxide ceramic material as a comparative example, the electrical performance test results of the ceramic samples prepared in the above 12 embodiments and 4 comparative example samples at corresponding temperatures are shown in Table 1:

[0088] Table 1 Statistical table of raw material composition of Examples 1-12 and electrical performance test results of Examples 1-12 and Comparative Examples

[0089]

[0090]

[0091] It can be seen that the volume resistivity of the ceramic samples prepared in Examples 1-12 is still higher than 160MΩ.cm even at a high temperature of 650°C. The ceramic samples prepared in this embodiment have high insulation performance and can meet the working condition requirement of not being broken down at high temperatures. However, high-purity magnesium oxide ceramic materials have a high risk of being broken down at high temperatures.

[0092] From the comparison between Examples 3 and 10-12, it can also be found that the higher the purity of magnesium oxide in the mixed material, the better the insulation property of the obtained insulating ceramic material.

[0093] Furthermore, in more embodiments, it was found that in the preparation process, the modifying reagents were selected from at least two of sodium stearate, sodium dodecyl sulfate, sodium dodecyl sulfonate, CTAB and butyl titanate, and a 40-100 mesh sieve was selected. The formed ceramic green sheets were subjected to a debinding treatment at a constant temperature of 500-700°C for 30-120 min, and the ceramic green sheets were heated to 1000-2000°C in a high-temperature muffle furnace and the temperature was kept constant for 1-48 h to perform high-temperature sintering on the ceramic green sheets, and insulating ceramic materials with insulating properties that meet the requirements can be obtained.

[0094] It should also be noted that the raw materials used to prepare the insulating ceramic materials involved in the embodiments of the present invention and the materials involved in the comparative examples are all commercially available general products.

[0095] The above description includes examples of one or more embodiments. Of course, it will be appreciated by those skilled in the art that the various embodiments may be further combined and arranged. Therefore, the embodiments described herein are intended to cover all such changes, modifications and variations that fall within the scope of protection of the appended claims. In addition, with respect to the term "comprising" used in the specification or claims, the word is encompassed in a manner similar to the term "including," as explained by "including," used as a transitional word in the claims. In addition, any term "or" used in the specification of the claims is intended to mean "non-exclusive or."

[0096] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the concept and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A downhole heater insulation material with improved insulation performance by manganese doping, characterized in that: The insulating material is an insulating ceramic material prepared by ball milling, drying and granulating, aging and molding, and plastic removal and sintering of a mixed material containing magnesium oxide, a doping material containing manganese elements and a modifying agent.

2. The downhole heater insulation material with improved insulation performance by manganese doping as claimed in claim 1, characterized in that: The mass content of the doping material containing manganese element in the mixed material is 0.5-2.7%, and the mass content of the modifying agent in the mixed material is 1-9%.

3. The downhole heater insulation material with improved insulation performance by manganese doping as claimed in claim 1, characterized in that: The doping material containing manganese element is manganese salt.

4. The downhole heater insulation material with improved insulation performance by manganese doping as claimed in claim 1, characterized in that: The doping material containing manganese element is manganese oxide.

5. The downhole heater insulation material with improved insulation performance by manganese doping as claimed in claim 1, characterized in that: The doping material containing manganese element is manganate.

6. The downhole heater insulation material with improved insulation performance by manganese doping as claimed in claim 1, characterized in that: The doping material containing the manganese element is a coordination compound of manganese.

7. The downhole heater insulation material with improved insulation performance by manganese doping as claimed in claim 1, characterized in that: The modifying agent is at least one of sodium stearate, sodium dodecyl sulfate, sodium dodecyl sulfonate, CTAB and butyl titanate.

8. A method for preparing an insulating material for a downhole heater with improved insulation performance by manganese doping, characterized in that: include: A mixed material including magnesium oxide, a doping material containing a manganese element and a modifying agent is subjected to wet ball milling to obtain a slurry raw material; Drying the slurry raw material and sieving it to obtain a powder material; Adding a binder into the powder material for granulation, and then pressing it into a ceramic green body; The ceramic green body is crushed, reshaped and aged to obtain a ceramic green sheet; The ceramic green sheets are subjected to plastic disassembly and sintering to obtain insulating ceramic materials.

9. The method according to claim 8, characterized in that After obtaining the ceramic green sheet, the method further comprises: Determine whether the particle size of the current ceramic green sheet meets the particle size requirements; If not, the current ceramic green sheet is used as the raw material and the process returns to the step of obtaining a slurry raw material through wet ball milling.

10. The method according to claim 8, characterized in that The slurry raw material obtained by wet ball milling comprises: The slurry raw material is obtained by wet ball milling with agate balls and anhydrous ethanol as media.

Citation Information

Patent Citations

  • High temperature stable X9R type multilayer ceramic capacitor dielectric material and preparation method thereof

    CN103936414A

  • Ceramic dielectric material of barium titanate core-strontium / zirconium / calcium shell structure and preparation method thereof

    CN107739205A

  • Preparation method of high-insulation and non-reducible dielectric material

    CN110002864A

  • High-aluminum black corundum ceramic material and preparation method thereof

    CN117923881A